Evolutionary characterization of clades 2.3.4.4 H5N6 and 2.3.2.1c H5N1 HPAI viruses in Vietnam (2013–2019) revealed distinct reassortants from distant spillovers - Trung Nam, Nguyen; Hung Chi, Nguyen; Hoang Ha, Chu; Thi Roan, Do; Bich Nga, Nguyen Thi; Thanh Hoa, Le (Vietnam Journal of Biotechnology, 2022)
Highly pathogenic avian influenza (HPAI) H5Nx viruses have continually undergone multiple evolutionary dynamics for the generation of various clades, subclades, and genotypes where 2.3.2.2c, and 2.3.4.4 become predominant and co-circulating in Vietnam from 2014 to date. In this study, fifteen H5 sequences in our study and 90 from others from different clades, 0, 1, 1.1, 2.3.2.1a, 2.3.2.1c, 2.3.4, 2.3.4.1, 2.3.4.2, 2.3.4.3 and 2.3.4.4 of H5N1, H5N2, H5N6, were characterized for hemagglutinin (HA) properties, genetic and phylogenetic analyses. Blast searching using the dataset of the full length of two H5N6 viruses revealed one strain, e.g., A/Duck/Vietnam/HT7/2014(H5N6) in May 2014, belonging to the Sichuan 2014-lineage of Group D (Minor). The other strain, A/Chicken/Vietnam/NT3/2017(H5N6)/or CkNT3-2017 in the Spring of 2017, belonged to the Japanese-Korean late 2016-cluster of Group C (Major). This cluster possessed 140NHETS-145del stretch of Leucine/Serine deletion at position 145 in HA1 (S/L145del), distinct from all the 2.3.4.4 H5N6 viruses known to date. There has been no report of the similar CkNT3-2017 of 2.3.4.4 reassortant in Vietnam prior to our study. The migration flyway might be the route for transportation of this novel H5N6 virus from Japan to Vietnam. In addition, the topology revealed another novel subclade of H5N6 (2018–2019) possibly, of the Vietnamese internal reassortments. The “H5Nx” viruses in Vietnam, in fact, have continually undergone multiple evolutionary processes in parallel with those lineages in China and East-Asia. Variations at the key sites in HA and altered genetic characteristics in novel HPAI H5Nx viruses in Vietnam present a caution for the vaccination program and the risk for human infection.